Prevalensi dan Faktor Risiko Infeksi Dirofilaria immitis pada Anjing yang Dipotong di Daerah Istimewa Yogyakarta (PREVALENCE AND RISK FACTOR OF THE DIROFILARIA IMMITIS INFECTION IN DOGS SLAUGHTERED IN DAERAH ISTIMEWA YOGYAKARTA) - Erawan, I G. Made Krisna; Tjahajati, Ida; Nurcahyo, Wisnu; Asmara, Widya (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.541, 2018)
The aim of this study was to determine the prevalence and risk factors Dirofilariaimmitis ( D. immitis ) infection in dogs slaughtered in Yogyakarta. A total of 151 dogs that were slaughtered from May – November 2013 were examined their heart in order to determine the presence of D. immitis infection. Blood samples were tested using Modified Knott’s Technique for microfilariae examination. The results showed that based on the heart and blood examination the prevalence of D. immitis infection was 14.6 % and 7.9 %, respectively. The risk factors for D. immitis infection were the age and origin of the dog.
Keywords: prevalensi, faktor risiko, Dirofilaria immitis, anjing, Yogyakarta